Immune response to SARS‐CoV‐2 in children: A review of the current knowledge. Issue 3 (17th August 2021) - Filippatos, Filippos; Tatsi, Elizabeth‐Barbara; Michos, Athanasios
ABSTRACT: Host immune responses to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), especially in children, are still under investigation. Children with coronavirus disease 2019 (COVID‐19) constitute a significant study group of immune responses as they rarely present with severe clinical manifestations, require hospitalization, or develop complications such as multisystem inflammatory syndrome in children (MIS‐C) associated with SARS‐CoV‐2 infection. The deciphering of children's immune responses during COVID‐19 infection will provide information about the protective mechanisms, while new potential targets for future therapies are likely to be revealed. Despite the limited immunological studies in children with COVID‐19, this review compares data between adults and children in terms of innate and adaptive immunity to SARS‐CoV‐2, discusses the possible reasons why children are mostly asymptomatic, and highlights unanswered or unclear immunological issues. Current evidence suggests that the activity of innate immunity seems to be crucial to the early phases of SARS‐CoV‐2 infection and adaptive memory immunity is vital to prevent reinfection. Abstract : Despite the limited immunological studies from children with COVID‐19, this review compares data between adults and children in terms of innate and adaptive immunity to SARS‐CoV‐2, discusses the possible reasons why children are mostly asymptomatic, and highlights unanswered or unclear immunological issues.